2018
DOI: 10.1128/aem.00052-18
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Antimicrobial Activity of Nisin-Based Lantibiotics against Gram-Negative Pathogens

Abstract: Lantibiotics are ribosomally synthesized and posttranslationally modified antimicrobial compounds containing lanthionine and methyl-lanthionine residues. Nisin, one of the most extensively studied and used lantibiotics, has been shown to display very potent activity against Gram-positive bacteria, and stable resistance is rarely observed. By binding to lipid II and forming pores in the membrane, nisin can cause the efflux of cellular constituents and inhibit cell wall biosynthesis. However, the activity of nis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 40 publications
7
88
0
2
Order By: Relevance
“…The Gly18Thr change is also interesting, as it is observed in nisins H, U, U 2 , P, and O 1-3 and is proposed to be modified to dehydrobutyrine (Dhb), in light of the dehydration observed in a M17Q-G18T derivative of nisin Z (29). At position 20, nisin J has a highly hydrophobic residue, phenylalanine, compared to the polar asparagine in nisin A. Li et al (30) found that extending the C terminus of nisin improves both its ability to permeate membranes and its inhibitory potential against Gram-negative bacteria. Therefore, nisin J's longer C terminus (compared to other nisin variants) could be more attracted to negatively charged cell membranes resulting in enhanced membrane insertion, which may be responsible for its broader host range.…”
Section: Discussionmentioning
confidence: 99%
“…The Gly18Thr change is also interesting, as it is observed in nisins H, U, U 2 , P, and O 1-3 and is proposed to be modified to dehydrobutyrine (Dhb), in light of the dehydration observed in a M17Q-G18T derivative of nisin Z (29). At position 20, nisin J has a highly hydrophobic residue, phenylalanine, compared to the polar asparagine in nisin A. Li et al (30) found that extending the C terminus of nisin improves both its ability to permeate membranes and its inhibitory potential against Gram-negative bacteria. Therefore, nisin J's longer C terminus (compared to other nisin variants) could be more attracted to negatively charged cell membranes resulting in enhanced membrane insertion, which may be responsible for its broader host range.…”
Section: Discussionmentioning
confidence: 99%
“…Bioengineering (engineering within the cell) and the use of synthetic biology‐based ( in vitro engineering) approaches have been important for advancing our understanding of the fundamentals of bacteriocin activity and structure–function relationships and also in designing novel peptides with enhanced functionalities (activity and/or stability) which make them more attractive from a clinical perspective (Cotter et al , ). Several examples of bioengineered variants of the prototypical lantibiotic nisin have been generated that provide examples of how lantibiotic functionality can be improved through single, or a small number of residue replacements (Kuipers et al , ; Healy et al , ; Ge et al , ; Zhou et al , ; Li et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…This polycyclic, 34 amino acid peptide (Fig. ) exhibits antibacterial activity against a wide range of Gram‐positive bacteria and a small number of Gram‐negative bacteria including Escherichia coli, Helicobacter pylori and Acinetobacter baumannii (Kim et al , , Kuwano et al , , Li et al ., ). Nisin exerts its antimicrobial activity both by pore formation and by inhibition of cell wall synthesis through specific binding to lipid II, an essential precursor of the bacterial cell wall (Breukink et al , ; Wiedemann et al , ; Hsu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Nisin, produced by Lactococcus lactis , has been shown to display very potent activity against Staphylococcus aureus ( S aureus ) and is the most extensively studied antibiotic and is used in the treatment of numerous diseases . Mare's milk is a popular traditional fermented milk from the Mongolian plateau that uses.…”
Section: Introductionmentioning
confidence: 99%